Diversity and Activity of Diazotrophs in Great Barrier Reef Surface Waters - Messer, Lauren F.; Brown, Mark V.; Furnas, Miles J.; Carney, Richard L.; McKinnon, A. D.; Seymour, Justin R. (Frontiers in Microbiology, 2017)
Discrepancies between bioavailable nitrogen (N) concentrations and phytoplankton growth rates in the oligotrophic waters of the Great Barrier Reef (GBR) suggest that undetermined N sources must play a significant role in supporting primary productivity. One such source could be biological dinitrogen (N2) fixation through the activity of “diazotrophic” bacterioplankton. Here, we investigated N2 fixation and diazotroph community composition over 10° S of latitude within GBR surface waters. Qualitative N2 fixation rates were found to be variable across the GBR but were relatively high in coastal, inner and outer GBR waters, reaching 51 nmol L-1 d-1. Diazotroph assemblages, identified by amplicon sequencing of the nifH gene, were dominated by the cyanobacterium Trichodesmium erythraeum, proteobacteria from the Gamma A clade, and -proteobacterial phylotypes related to sulfate-reducing genera. However, diazotroph communities exhibited significant spatial heterogeneity, correlated with shifts in dissolved inorganic nutrient concentrations. Specifically, heterotrophic diazotrophs generally increased in relative abundance with increasing concentrations of phosphate and N, while Trichodesmium was proportionally more abundant when concentrations of these nutrients were low. This study provides the first in-depth characterisation of diazotroph community composition and N2 fixation dynamics within the oligotrophic, N-limited surface waters of the GBR. Our observations highlight the need to re-evaluate N cycling dynamics within oligotrophic coral reef systems, to include diverse N2 fixing assemblages as a potentially significant source of dissolved N within the water column.